Nanotechnology in Periodontics: An Overview (Medico Legal Update, 2020)
Nanotechnology is a booming field during recent years in medicine and dentistry. Application ofnanotechnology in Periodontics is referred to as nanoperiodontics. Nanoscale materials show superiorquality and outcome than traditional materials used in almost all areas including diagnosis, prevention,treatment, drug delivery and in dental implant coatings. This article will overview the history, classification,synthesis, applications, toxicity and future of nanoperiodontics.